THE CLIMATE IN ARAGÓN BY WAY OF WEATHER SAYINGS - Lolumo García, Eduardo (Geographicalia, 2021)
Climate and weather in Aragón can be described and evenexplainedbyway of thesayingsorproverbsthatthroughoutcenturies country folk has usedderivedfromtheirobservation and experience. These are resumed in simple sayingseasy to remember as a way to helpfuturegenerations to havesome ‘control’ in predictingweatherorhaving a betterknowledge of theclimate. Todaytheseproverbsrelating to theweathercontainallthecollectivewisdom of thosewhooriginatedthem. Eventhoughmany of themlackthescientificprecisionthatpresentsciencesregardingweather and climaterequire, theyconstitute a basictoolthatgoesfarbeyond a simple easyrhyme and deserveanattention and reflectionthattranscendbelieves and superstitions. They are basedonexperience, themother of allsciences.